Expression of methyl farnesoate epoxidase (Mfe) and juvenile hormone esterase (jhe) genes and their relation to social organization in the stingless bee melipona interrupta (hymenoptera: Apidae) - Brito, Diana Vieira; da Silva, Carlos Gustavo Nunes; Rêgo, Livia Cristina Neves; Zilse, Gislene Almeida Carvalho (Genetics and Molecular Biology, 2021)
Social organization in highly eusocial bees relies upon two important processes: caste differentiation in female larvae, and age polyethism in adult workers. Juvenile Hormone (JH) is a key regulator of both processes. Here we investigated the expression of two genes involved in JH metabolism – mfe (biosynthesis) and jhe (degradation) – in the context of social organization in the stingless bee Melipona interrupta. We found evidence that the expression of mfe and jhe genes is related to changes in JH levels during late larval development, where caste determination occurs. Also, both mfe and jhe were upregulated when workers engage in intranidal tasks, but only jhe expression was downregulated at the transition from nursing to foraging activities. This relation is different than expected, considering recent reports of lower JH levels in foragers than nurses in the closely related species Melipona scutellaris. Our findings suggest that highly eusocial bees have different mechanisms to regulate JH and, thus, to maintain their level of social organization. © Sociedade Brasileira de Genética.